A new species of Xenobatrachus (Anura, Microhylidae) with a striking resemblance to Xenorhina bouwensi - Günther, Rainer; Knop, Ronny (Zootaxa, 2006)
The micohylid frog Xenobatrachus lanthanites sp. nov. is described on the basis of recently collected material from the mountains of Yapen Island in Cenderawasih Bay, Papua, Province of Indonesia. With a mean snout-urostyle length of 21.9 mm, the new species is among the smallest of its genus. In most morphological, anatomical, ecological and behavioural details it is very similar to Xenorhina bouwensi (de Witte) from the mainland of north-western New Guinea. Data for the latter are also given. Biochemical studies did not furnish unequivocal results concerning the taxonomic status of the genus Xenobatrachus.